MECHANICAL PROPERTIES OF CELLULOSE BACTERIA FROM COCONUT WATER WITH ADDITION OF THE CHITOSAN - Rahayu, Tutiek; Rohaeti, Eli (Jurnal Penelitian Saintek, 2015)
The objective of this research were to identify the chitosan concentration that produced bacterial cellulose-chitosan with optimum mechanical properties and to identtify the effect of chitosan addition for function group, cross section morphology, and crystallinity of bacterial cellulose based coconut water. Bacterial cellulose-chitosan has been succesfully prepared by immersing dry bacterial cellulose in chitosan solution 0.5; 1.0; 1.5; 2.0; 2.5; and 3.0% (m/v) for 6 hours. The films were characterized using tensile tester to identify mechanical properties, XRD (X-Ray Diffraction) to identify crystallinity, FTIR (Fourier Transform Infrared) to identify functional group, and SEM (Scanning Electron Microscope) to identify cross section morphology. The bacterial cellulose-chitosan 0.5% had the most optimum mechanical properties. The addition of chitosan could decrease elongation at break, and also increase strenght at break and modulus Young of bacterial cellulose. The crystalinity decreased with the addition of chitosan 0.5% from 30.43% to 15.38%. On the other hand, the FTIR spectrum showed that there was interaction between bacterial cellulose and chitosan molecule. SEM images show that bacterial cellulose consisted of tight fibrin thread, so it could form layers. Bacterial cellulose-chitosan 0.5% consisted of multilayered of bacterial cellulose and chitosan layers.